2014
DOI: 10.1044/1059-0889(2013/13-0018)
|View full text |Cite
|
Sign up to set email alerts
|

X-Linked Deafness-2 (DFNX2) Phenotype Associated With a Paracentric Inversion Upstream of POU3F4

Abstract: Purpose The authors report a seven-year-old male, designated FR, with severe sensorineural hearing loss. Features include round face, hypertelorism, epicanthal folds, and flat nasal root. Although there were early developmental concerns, all but his speech delay resolved when he was placed in an educational program that accommodated his hearing loss. To investigate genetic causes for his hearing loss, genetic studies were performed. Methods History, physical examination, audiologic assessment, and imaging we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…In addition, despite the possible effects on fertility owing to the unbalanced chromosomes resulting from a crossover within the inverted region in heterozygotes, for some of these inversions no increased risk for miscarriage or problems in chromosome segregation during meiosis have been observed [ 55 , 56 ]. Not all inversions are harmless, however, and several diseases have been found to be occasionally caused by inversions, mostly by direct disruption of one gene [ 57 , 58 ] or by altering its gene expression [ 59 , 60 ]. These inversions appear de novo in patients or are inherited mutations restricted to a given family, and thus they do not represent polymorphic variants segregating in human populations.…”
Section: Inversions As Simple Mutations Causing Diseasementioning
confidence: 99%
“…In addition, despite the possible effects on fertility owing to the unbalanced chromosomes resulting from a crossover within the inverted region in heterozygotes, for some of these inversions no increased risk for miscarriage or problems in chromosome segregation during meiosis have been observed [ 55 , 56 ]. Not all inversions are harmless, however, and several diseases have been found to be occasionally caused by inversions, mostly by direct disruption of one gene [ 57 , 58 ] or by altering its gene expression [ 59 , 60 ]. These inversions appear de novo in patients or are inherited mutations restricted to a given family, and thus they do not represent polymorphic variants segregating in human populations.…”
Section: Inversions As Simple Mutations Causing Diseasementioning
confidence: 99%
“…Structural variants upstream the coding POU3F4 region, including microdeletions, inversions, and duplications, have also been reported in patients with similar hearing loss phenotypes, thus indicating the presence of cis -regulatory elements (e.g. enhancers) within those regions (even up to 900kb upstream), which if disturbed result in altered POU3F4 expression through LRPE [ 25 – 27 ]. The majority of POU3F4 disruption cases have been reported in affected males.…”
Section: Discussionmentioning
confidence: 99%
“…The X-linked POU3F4 gene is the first nuclear gene implicated in nonsyndromic deafness. The type of HL may be SNHL or mixed and associated with IP-III (incomplete partition type 3), cochlear hypoplasia, and/or stapes fixation (DFN3) (36,37,38,39). In addition to mutations located within the gene, copy number variants not involving the coding part of the gene have been reported; de Kok et al (40) identified a hot spot for microdeletions in patients with X-linked deafness 900 kb proximal to the DFN3 gene.…”
Section: Classification Of Inner Ear Anomaliesmentioning
confidence: 99%